DIETARY INFLUENCE ON INR LEVELS IN ANTICOAGULATED PATIENTS (International Journal of Food and Nutritional Sciences, 2022)
Objective:The international normalized ratio (INR) is the primary test for anticoagulation patients. It can also be used to evaluate the patients' coagulation state or bleeding risk. The international normalized ratio (INR) values and, consequently, the dose of warfarin are influenced by a number of variables, including vitamin K intake in diet, medication and herb interactions, disease conditions, and alcohol consumption. The aim of this study is to identify how dietary intake affects changes in INR.